PERAN PSYCHOLOGICAL SAFETY TERHADAP WORK ENGAGEMENT DENGAN SELF-ESTEEM SEBAGAI MEDIATOR PADA KARYAWAN - Cheryl Avril Firdiani; Reza Fahlevi; Zamralita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of psychological safety on work engagement, with self-esteem serving as a mediating variable among employees in Indonesia. A quantitative approach was employed, involving 283 respondents with a minimum of one year of work experience. The instruments used in this research included the Utrecht Work Engagement Scale (UWES), the Psychological Safety Scale (Plouffe, 2023), and the adapted Rosenberg Self-Esteem Scale (RSES). Data were analyzed using SPSS and PROCESS Model 4. The findings indicate that both work engagement and psychological safety fall into the high category, while self-esteem is categorized as low yet remains above the hypothetical mean. Psychological safety has a positive and significant effect on work engagement (R² = 0.2683). Self-esteem also demonstrates a positive and significant effect on work engagement. Furthermore, psychological safety positively affects self-esteem, although the contribution is relatively small. Mediation analysis reveals that self-esteem partially mediates the relationship between psychological safety and work engagement, as indicated by a significant indirect effect based on bootstrapping results (BootLLCI = 0.0074; BootULCI = 0.0656). These findings highlight the importance of a psychologically safe work environment and positive self-evaluation in enhancing work engagement. The study provides practical implications for organizations to strengthen supportive work cultures and implement interventions aimed at improving employees’ self-esteem.